ASSESSING THE PROTECTIVE ROLE OF SILYMARIN FROM MILK THISTLE AGAINST BUSULFAN-INDUCED OXIDATIVE STRESS AND LIVER DYSFUNCTION IN EGYPTIAN RATS - Amina , Mahmoud El-Sayed (Global Journal of Medical and Health Science, 2023)
Busulfan, a chemotherapeutic agent widely used in conditioning regimens for hematopoietic stem cell transplantation, is known to induce oxidative stress and liver dysfunction. This study aimed to assess the protective role of Silymarin, an herbal extract from Milk Thistle (Silybum marianum), against Busulfan-induced liver damage and oxidative stress in Egyptian rats. Thirty male Egyptian rats were divided into three groups: a control group, a Busulfan-treated group, and a Silymarin-treated group. The Busulfan-treated group received a single dose of Busulfan, while the Silymarin-treated group received Silymarin orally for 14 days before Busulfan administration. After 14 days, the rats were sacrificed, and liver tissues were collected for analysis. Our results demonstrated that Busulfan administration led to a significant increase in oxidative stress markers, such as malondialdehyde (MDA) levels, and a decrease in antioxidant enzyme activities, including superoxide dismutase (SOD) and glutathione peroxidase (GPx). Moreover, Busulfan-induced liver damage was evident through elevated liver enzymes, such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST), as well as histopathological changes. Conversely, the Silymarin-treated group exhibited significantly lower MDA levels and improved antioxidant enzyme activities compared to the Busulfan-treated group. Furthermore, Silymarin pre-treatment ameliorated liver dysfunction, as evidenced by reduced ALT and AST levels and histological improvements in liver tissues. In conclusion, Silymarin from Milk Thistle demonstrated a protective effect against Busulfan-induced oxidative stress and liver dysfunction in Egyptian rats. These findings suggest the potential utility of Silymarin as an adjunct therapy to mitigate the adverse effects of Busulfan in clinical settings, particularly in the context of hematopoietic stem cell transplantation. Further research is needed to elucidate the underlying mechanisms of Silymarin’s protective actions and its clinical applicability.